Equity, Inclusion, and Faculty Hiring Committees - Jill Channing (Academic Chairpersons Conference Proceedings, 2023)
Issues of explicit and implicit bias pervade hiring processes for faculty members. This session focuses on creating equitable and inclusive faculty hiring processes and practices. Practices include defining and recognizing bias, adhering to university policies, and addressing equity during committee deliberations and decision-making processes.
Keywords: Race and hiring; Hiring and equity; Equity and inclusion in employment; leadership processes; Equity; inclusion; and higher education